SOLAR BATTERY STORAGE SYSTEM - Ab Rahman, Firdaus (Universiti Teknologi PETRONAS, 2016)
In the present day battery storage is crucial in all individual power network structures. Their effectiveness and life time affects the overall photovoltaic system performance and economics. Batteries specified particularly for use in photovoltaic systems have to be distinguished with standing of a very deep discharge rate and high cycling stability. The suitable types of the rechargeable batteries are discussed, and the most essential features of lead acid battery required for assessment of the performance are presented and deliberated in this project. Choosing the optimal circumstances of lead acid battery to gain the maximum efficiency, ampere hour and watt hour capacities by applied measurements on lead acid battery. The internal resistance of the battery is the dependable fundamental for determine the state of charged and discharged.